The Influence of Education, Family Income, and Family Planning Participation on Mother's Decision to Work in Kb Kedampul Village, Duwet Village, Malang Regency - Ula, Apriliana Nurlatifah; Susilo, Singgih; Soelistijo, Djoko; Wahyudi, Adip (Future Space: Studies in Geo-Education, 2025)
A mother’s decision to engage in employment carries significant social and economic implications for both the family and the individual. This study aims to examine the influence of education level, family income, and participation in family planning programs on mothers’ decisions to work in Kedampul Village, Duwet Subdistrict, Malang Regency. A quantitative research design was employed, utilizing logistic regression analysis to investigate these relationships among 77 respondents. The results indicate that education level and participation in family planning programs do not significantly affect mothers’ decisions to work. Conversely, family income has a significant influence, where lower family income increases the likelihood of maternal employment. These findings highlight the predominance of economic factors over educational attainment and family planning participation in shaping maternal labor force participation in this rural context. This study offers insights for policymakers and stakeholders focused on women’s empowerment and family welfare in similar socio-economic settings.